Improving The Capacity of Journal Article Writing of Indonesian Teachers in Jeddah Indonesian School - Fafurida; Karsinah; Bowo, Prasetyo Ari (Universitas Negeri Semarang, 2024)
The background of this service activity was the limited ability of Indonesian teachers teaching in Jeddah to write scientific journal articles, which was caused by low motivation and a lack of knowledge about good and correct article-writing techniques. This service aimed to equip teachers in Jeddah with the journal article writing skills needed for professional development. The main target of this activity was teachers in Jeddah. The methods applied in this service included online training and mentoring, with an in-service training (IST) and on-service training (OST) approach. The process of implementing activities included several stages, namely preparation, training, mentoring, monitoring, and evaluation. The results of this activity showed a significant improvement in the ability to write journal articles among teachers in Jeddah. They became more confident in their writing and were able to produce quality articles ready to be published in national journals.